A new look at the supposed risks of early institutional rearing. Issue 1 (22nd June 2017) - Woodhouse, S.; Miah, A.; Rutter, M.
Abstract : The main focus is on the assessment of the effects of early institutional care and compares three longitudinal studies from Romania, Greece and Hong Kong/China. The findings have been strikingly contrasting. The review asks if the risks are dependent on whether or not the institutional rearing is accompanied by gross pervasive deprivation (as it was in Romania) and investigates the methodological issues to explore the causal influence of the outcomes. Evidence is considered on changing institutional practices and the benefits of doing so. Comparison is made between institutions with major deprivation and those without global deprivation. A small number of studies are discussed that look at direct comparisons between institutional and community care. The empirical and conceptual implications of the findings are discussed.